A steel hysteretic damper for seismic design and retrofit of precast portal frames. (1st October 2022) - Javidan, Mohammad Mahdi; Ali, Amir; Kim, Jinkoo
Abstract: In this paper a steel hysteretic damper is proposed which can be installed at the beam-column joint of precast concrete structures and can greatly improve the seismic performance of these structures. The damper is made of a few steel plates with reduced sections placed in parallel, which yield under in-plane bending caused by joint rotation and dissipate energy induced by seismic activity. As less attention has been paid to seismic performance evaluation and design of precast portal frames, a procedure for design and performance estimation is established based on the available theoretical formulation and is verified by comparing their results with those obtained by analysis. The efficiency of the proposed damper is investigated by retrofitting a portal frame and evaluating its seismic performance before and after retrofit. The results show that the developed damper can significantly reduce the maximum interstory drift ratio and prevent the global collapse of the structure, which is of particular interest in practice. The hysteretic behavior and the energy dissipation capability of the frame are compared before and after the retrofit. It is observed that most of the seismic energy is dissipated by the dampers installed in the retrofitted frame, which protects the frame against seismic damage. Highlights: A steel hysteretic damper is proposed which can be installed at the beam-column joint of precast concrete structures. The damper is made of a few L-shaped steel plates with reduced sections placed in parallel. The theoretical formulation of the damper and a design procedure are established and verified by numerical analysis. The damper can reduce the maximum interstory drift ratio and prevent the global collapse of the structure.